2013
DOI: 10.1093/neuonc/not028
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD163 prevents apoptosis through the production of granulocyte colony-stimulating factor in meningioma

Abstract: To our knowledge, this is the first report that demonstrates CD163 expression in meningioma not only by immunohistochemistry but also by reverse-transcription polymerase chain reaction, using primary culture cells, and provides the novel molecular function of CD163 to prevent apoptosis through the production of G-CSF in meningioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 51 publications
1
21
1
Order By: Relevance
“…Variable levels of infiltrating tissue macrophages in meningioma have been previously reported. CD163 is a well-established M2 macrophage marker and has previously been shown using immunohistochemistry to be in high abundance in atypical grade II meningiomas [27,40] but, unlike previous authors, we correlated CD68 (Figure 3) and CD163 expression with NF2 status (Figure 4). Our short-term cell culture data were corroborated by IHC analysis.…”
Section: Discussioncontrasting
confidence: 54%
“…Variable levels of infiltrating tissue macrophages in meningioma have been previously reported. CD163 is a well-established M2 macrophage marker and has previously been shown using immunohistochemistry to be in high abundance in atypical grade II meningiomas [27,40] but, unlike previous authors, we correlated CD68 (Figure 3) and CD163 expression with NF2 status (Figure 4). Our short-term cell culture data were corroborated by IHC analysis.…”
Section: Discussioncontrasting
confidence: 54%
“…Fifty-two percent of meningiomas were immunohistochemically positive for CD163, including Grade I (48.5%) and Grade II (71.4%) tumors, and its expression correlated with histological atypical parameters that directly predict the prognosis of meningioma. 105) In nude mice, CD163-overexpressing meningioma cells showed significant suppression of apoptosis and accelerated tumor growth. 105) …”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The presence of CD163 + macrophages was suggested to have a stronger association with less favorable clinicopathological features than CD68 + macrophages (Medrek, Ponten, Jirstrom, & Leandersson, 2012). Numerous studies demonstrate that elevated CD163 expression correlates with advanced cancer stages, unfavorable prognosis, early distant recurrence, and reduced patient survival in various types of cancer, which include melanoma (Jensen et al, 2009), meningioma (Kanno et al, 2013), breast cancer (Mansfield, Heikkila, von Smitten, Vakkila, & Leidenius, 2012; Shabo, Stal, Olsson, Dore, & Svanvik, 2008; Tiainen et al, 2014), colorectal cancer (Edin et al, 2012; Shabo, Olsson, Elkarim, Sun, & Svanvik, 2014), oral squamous cell carcinoma (He, Bao, et al, 2014; Wang et al, 2014), ovarian carcinoma (Reinartz et al, 2014), HCC (Kong et al, 2013), angiosarcoma (Fujimura et al, 2013), glioma (Komohara et al, 2008), and gastrointestinal stromal tumors (van Dongen et al, 2010), and hematopoietic malignancies, such as T cell leukemia/lymphoma (Komohara et al, 2013), acute myeloid leukemia (Garcia, Gardner, & Reichard, 2008), and classical Hodgkin lymphoma (Klein et al, 2014; Koh, Park, Yoon, Suh, & Huh, 2014). A recent study showed that relapse of head and neck cancer after chemoradiotherapy also correlated with CD163 + macrophages in primary tumor and CD11b + myeloid cells in recurrences (Balermpas et al, 2014).…”
Section: Scavenger Receptors In Cancer Immunobiologymentioning
confidence: 99%
“…Several studies reported that the tumor cell itself in breast cancer, rectal cancer, bladder cancer, and meningioma expresses CD163 and that the CD163 levels are associated with metastatic grade, early recurrence, and reduced patient survival (Kanno et al, 2013; Maniecki et al, 2012; Shabo, Olsson, Sun, & Svanvik, 2009; Shabo et al, 2008). It was found that IR-induced CD163 expression on tumor cells rendered these cells more resistant to radiotherapy (Shabo et al, 2008).…”
Section: Scavenger Receptors In Cancer Immunobiologymentioning
confidence: 99%
See 1 more Smart Citation